KONSELING PASTORAL UNTUK GENERASI DIGITAL BERDASARKAN EFESUS 5:15-16 - Anastasya Lilianti; Yusrianto Parapasan, Grefi Penang, Lenianti Rissing, Nuryana Tanan (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The digital generation today faces significant challenges, such as technology addiction, social isolation, and the search for meaning in life, which is often distorted by the virtual world. This study aims to explore the role of pastoral counseling in helping the digital generation overcome these challenges, based on the principles found in Ephesians 5:15-16. This verse teaches the importance of living wisely and making good use of time, which is relevant in a digital context full of distractions. Using the literature review method, this study analyzes works that discuss pastoral counseling, the challenges of the digital generation, and biblical applications in daily life. The findings suggest that pastoral counseling based on Ephesians 5:15-16 can provide practical guidance for individuals to manage time, relationships, and technology wisely, as well as discover true meaning in life. This study emphasizes the importance of a pastoral approach in helping the digital generation live more balanced and responsible lives, integrating Christian faith values into their lives.